2016
DOI: 10.1021/acs.nanolett.5b03822
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Nonlinear Coupling between Orthogonal Flexural Modes of a Pristine GaAs Nanowire

Abstract: We demonstrate nonlinear coupling between two orthogonal flexural modes of single as-grown GaAs nanowires. The resonant frequency of one mode can be shifted over many line widths by mechanically driving the other mode. We present time-domain measurements of the mode coupling and characterize it further by pump−probe experiments. Measurements show that a geometric nonlinearity causes the frequency of one mode to depend directly on the square amplitude of the other mode. Nearly degenerate orthogonal modes in nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…The splitting between the modes is many times their linewidths, a property observed in several measured NWs. Finite element modeling (FEM) has shown that even small cross-sectional asymmetries (< 1%) or clamping asymmetries can lead to mode splittings similar to those observed [27].…”
Section: Nanowire Force Sensorsmentioning
confidence: 83%
“…The splitting between the modes is many times their linewidths, a property observed in several measured NWs. Finite element modeling (FEM) has shown that even small cross-sectional asymmetries (< 1%) or clamping asymmetries can lead to mode splittings similar to those observed [27].…”
Section: Nanowire Force Sensorsmentioning
confidence: 83%
“…For the sake of completeness, we also added the sum over the other family of transverse modes (in y direction), which coefficients are designed with a bar, and the index with a prime (the position standard deviation simply writes ∆y 2 m ). Indeed, the nonlinear coupling between flexural modes of different families has been studied recently [50]. We shall not discuss the coupling to longitudinal and torsional modes, which is outside of the scope of beam mechanics; these depend directly on the Poisson's ratio, and shall be very weak.…”
Section: Application To a Thermalized Family Of Modesmentioning
confidence: 99%
“…In this article, we expose a novel ultrasensitive measurement technique going beyond scalar measurements and permitting to directly image vectorial 2D force fields. It is based on a singly clamped nanowire (NW) which can oscillate along two perpendicular transverse directions [18,[20][21][22][23][24]. Its vibrating extremity is immersed in the force field under investigation while its 2D-Brownian motion is optically detected and reconstructed in realtime.…”
mentioning
confidence: 99%